Supremacy of Translation over Writing: A Psycholinguistic Analysis - Ziahosseiny, S.M. (Iranian Journal of Translation Studies, 2003)
Through an analysis and comparison of the mental processes involved in writing a piece of literary text, and then translating it into another language, it was found that a translator is involved in many more such subtle mental behaviours: a) comprehending the original text; b) finding the linguistic equivalents in the target language to convey the similar message and beauty in the mind of the reader of the translated text. It is concluded that the translator has supremacy over the writer with respect to mentality as well as social prestige, though both enjoy a high rank in civilized communities.